Effect of Insertion Techniques on the Shear Bond of Low Shrinkage Composite Restorative Materials - Abdelmawla, Asma; El-Hejazi, Ahmed (Libyan Journal of Dentistry, 2020)
ABSTRACT Background: Dental composite has been used in dentistry offering a significant number of benefits and advantages. However, the polymerization shrinkage remains a major drawback of these materials which effect on their bond strength. Objectives: this study aimed to evaluate the shear bond strength (SBS) of low shrinkage composite with different insertion techniques (layering and bulk) using two storage condi- tions (wet and dry) then compare them with conventional methacrylate composites. Methods: one handed and eight cylindrical shaped specimens were fabricated from three different types of dental composite di- vided into 12 groups according to insertion technique and the storage condition (n=9/groups). Shear test were carried out using universal testing machine with speed of 0.5mm/min. Data were analyzed using one- way ANOVA and the Tukey test. The fractured surfaces of the test samples were visually evaluated using light microscope at 20 and 40 magnifications and classified their fracture into adhesive, cohesive or mixed. Results: Filtek Supreme composite inserted in bulk technique and stored dry showed the highest values (36.45 MPa). Silorane and Tetric Ceram composites were lower in their all groups except for specimens inserted in layers was further decreased by wet storage (21.90, 21.35 MPa). Conclusion: It can be concluded that insertion technique and storage condition type didn’t significantly affect SBS of Silorane resin in comparison with other methacrylate resins, except for the specimens inserted in layers and wet condition, there was a significant decrease in SBS values.